Local structure elucidation and reaction mechanism of light naphtha aromatization over Ga embedded H-ZSM-5 zeolite: Combined DFT and experimental study - Wongnongwa, Yutthana; Kidkhunthod, Pinit; Sukkha, Usa; Pengpanich, Sitthiphong; Thavornprasert, Kaew arpha; Phupanit, Jakkrapong; Kungwan, Nawee; Feng, Gang; Keawin, Tinnagon; Jungsuttiwong, Siriporn (My University, 2020)
Local structures and mechanisms for n-pentane aromatization on Ga embedded H-ZSM-5 zeolite (Ga/ZSM-5) were elucidated using Synchrotron-based X-ray absorption spectroscopy (XAS) and density functional theory (DFT) calculations to understand the role of Ga/ZSM-5 zeolite in aromatics synthesis. XAS data suggests that Ga ligates with four oxygen or four hydrogen atoms. Catalytic tests results suggest that conversion by Ga/ZSM-5 catalyst cannot occur via C6–C8 non-aromatic intermediates, while the availability of Ga metal sites promotes the aromatization of C2 and C3 species. Therefore, conversion of n-pentane to benzene or toluene comprises four steps, i) cracking, ii) GaH2 activation, iii) cyclization, and iv) dehydrogenation. Our model predicts the key intermediate in n-pentane aromatization on Ga/ZSM-5 zeolite to be a five-membered Ga-C4 ring structure. The ring undergoes expansion to form a seven-membered Ga-C6 ring. Moreover, we discuss thermodynamics and kinetic results for the benzene and toluene formation pathways. Our results provide new finding for the role of Ga/ZSM-5 zeolites in n-pentane aromatization processes.
Keywords: DFT; Ga/ZSM-5; Pentane aromatization